(untitled) (Québec, 1997)
This book introduce low-level image processing - an information theory stand point. Application of regularzatin methods to cardio-Vascular imaging. Modeling and optimization in bayesian tomographic reconstrution...
Keywords: Chẩn đoán hình ảnh,Diagnostic imaging; Kỹ thuật số,Digital techniques